Book Review: Priemus, H., Flyvbjerg, B. and Van Wee, B. (eds.) Decision-Making on Mega-Projects – Cost-Benefit Analysis, Planning and Innovation - Nijkamp, Peter (European Journal of Transport and Infrastructure Research, 2008)
Mega-projects take place in many domains of public policy. Examples are airports, artificial islands, new underground systems, river front developments, new motorways or railways, and so forth. Such mega-projects are not only characterized by large sums of (often public) money spent, but also by complexity, uncertainty, long duration, spatial spillovers and multiple actors or stakeholders. A particularly intriguing feature of mega-projects is that normally the actual costs are far higher than the anticipated or estimated costs. This creates always some suspicion on the solidity of the planning and implementation of such projects, in particular because it is at the end the taxpayer who is the victim.